ANATOMO-MORPHOLOGICAL STUDY AND NEW ORIGINAL CLASSIFICATION OF CONCHA BULLOSA - Alin Horatiu Nedelcu; Loredana Liliana Hurjui; Marius Constantin Moraru; Cristinel Ionel Stan; Carmen Marinela Cumpat; Ileana Ioniuc; Razvan Tudor Tepordei; Cristina Claudia Tarniceriu (Romanian Society of Oral Rehabilitation, 2024)
Introduction. The pneumatized cavities of the skull are characterized by the presence of numerous anatomical variants. Among these, the aberrant pneumatization of the middle turbinate is noteworthy, both in terms of prevalence and in terms of clinical resounding. The identification of this anomaly can be achieved clinically through anterior or posterior rhinoscopy, but the diagnostic gold standard is represented by spiral computer tomography (CT) and cone-beam computed tomography (CBCT) scans. Our study aims to determine the prevalence of concha bullosa (CB) in the Romanian population and to observe the distribution of the anomaly according to sex and age groups. Secondarily, we propose a new clinical classification based on the morphological appearance of concha bullosa. The selected cases will be distributed according to this new classification. Thirdly, we will study the association of concha bullosa with rhinosinusitis. Materials and methods. Our retrospective randomized study included 105 CT scans of non-traumatic patients (mean 60.34 ± 20.48 years) who underwent cranio-cerebral examinations between 01.07.2023 - 31.12.2023 in the Iasi Clinical Rehabilitation Hospital. Results. Concha bullosa was identified in 57 patients out of 106 (53.77%). Among them, 30 (28.3%) had the bilateral form and 27 (25.47%) the unilateral form. The applied statistical tests demonstrated a uniform distribution by age and gender groups. Within the classification proposed by us, we have identified all nine subtypes. Between subtypes I (A, B, C) and subtypes II (A, B, C), we recorded statistical significance (p = 0.00092), with the predominance of the lamellar type over the bulbous type. Conclusions. Concha bullosa has a high prevalence in the studied cohort. It does not show variations related to age or sex, which supports the malformative origin. The classification proposed by us ensures a better picture of the local mass effect determined by CB.